Hybrid Antimicrobial Peptide Targeting Staphylococcus aureus and Displaying Anti-infective Activity in a Murine Model - Shang, Lu; Li, Jiawei; Song, Chunsheng; Nina, Zaytseva; Li, Qiuke; Chou, Shuli; Wang, Zhihua; Shan, Anshan (Frontiers in Microbiology, 2020)
Broad-spectrum antimicrobial peptides (AMPs) kill bacteria indiscriminately, increasing the possibility of the ecological imbalance in microbiota. To solve the above problem, targeting AMPs was proposed that kill pathogenic bacteria without breaking the micro-ecological balance of the body. Here, we successfully designed a targeting antimicrobial peptide S2, which is a fusion peptide composed of the targeting domain from modified autoinducing polypeptide and the killing domain of the known antimicrobial peptide. The targeting domain can guide fusion peptide to selectively recognize the S. aureus with little effect on the other members of the resident flora. Contrary to conventional antibiotics, S2 hardly induced drug resistance, even with repeated incubation of S. aureus at sub-MIC levels. Mechanism studies indicated that S2 killed S. aureus by destroying the bacterial membrane. Meanwhile, S2 possessed excellent salt-tolerance properties and biocompatibility. Importantly, S2 exhibited prefect treatment efficacy against S. aureus subcutaneous infection model and remained nontoxic. In conclusion, this study provides a promising strategy for designing targeting AMPs against growing concerned bacterial infections.